Surgical outcome of 60 operated patients with acute extradural hematomas based on the preoperative glasgow coma scale - Ajaydeep Singh; Arvinpreet Kour; G S Bindra; Ajay K Gehlot; Rahul Midha; Kartik Nandra (Apollo Medicine)
Aim and Objective: This study aims to evaluate the outcome of the patients operated for acute extradural hematoma (EDH). Patients and Methods: Sixty consecutive cases of acute EDH were treated at medical college hospital to assess the outcome of the patients based on their Glasgow Coma Scale (GCS), radiological assessment, and pupil size. The patients were monitored of their GCS, pupillary size, and vitals. The Glasgow outcome scale was used to evaluate patient outcome at the discharge from the hospital and after 3 months. Observation and Results: Sixty patients constituting 56 males and 4 females were the part of the study. The mean age of the patients was 23.21 years (range: 2–47 years). On an average, the patients were operated around 9.91 h after the trauma (ranging 2–24 h). Out of sixty patients, 25, 17, and 18 patients had GCS of mild, moderate, and severe groups. Prompt surgery with better care obtained us with mortality 1.6%, morbidity 21.7%, and complete recovery in 83% patients. Conclusion: We may conclude in our study that presurgical clinical findings such as sensorium of patient and pupillary status were an important indicator for surgical outcome. In most of the cases, the outcome was favorable with progressive recovery.